Maximizing the crop wild relative resources available to plant breeders for crop improvement - Maxted, Nigel; Magos Brehm, Joana (Frontiers in Sustainable Food Systems, 2023)
Crop breeders are currently facing the need to continue increasing crop production to feed the growing human population, while mitigating the negative impacts of climate change on agriculture. Taxonomic and genetic diversity, which includes taxa, genes and alleles that offer novel sources of resistance to pests, disease and abiotic factors that affect crop quality and quantity, are a key tool for crop breeders to address these challenges. Lack of access to this diversity is currently limiting crop improvement. This paper focuses on how the breeder's requirement for greater diversity may be met despite the continue challenges of growing human population, and the impacts of climate change. It is argued that gene pool diversity is largely concentrated in crop wild relatives (CWR) and their more active conservation, especially focusing on in situ conservation applications, will enable the breeding challenges to be met. Further, that the science of in situ conservation is only now coming of age but is sufficiently advanced to facilitate the establishment of integrated national, regional, and global in situ CWR conservation networks. For humankind to substantially benefit from the additional adaptive diversity made available through these collaborative networks for CWR in situ conservation for the first time, breeders need to be provided with the critical resources necessary to address the negative impacts of climate changes on food production—therefore promoting greater global food security.